NEGLECTED COXITIS TUBERCULOSA MANAGEMENT IN CHILDREN - Sulis Bayusentono; Erwin Ramawan; Henry Dominica (Universitas Airlangga, 2019)
Background: Tuberculosis is one of serious health problems throughout the world, including in Indonesia. The incidence of tuberculosis continue to increase annually, especially the case of bone tuberculosis which is part of tuberculosis extra pulmonary as much as 10-20%.Case: A case report of 2 years old girl, with a neglected posterior hip dextra et causa coxitis tuberculosa dextra in Dr. Soetomo General Hospital, in period October 2013 until September 2015. Data were taken from the retrospective medical record through the anamnesis, physical findings, radiological, and laboratory examinations.Discussion: A 2 years old girl diagnosed as Neglected Posterior Hip dextra et causa Coxitis TB dextra, carried out of open biopsy, debridement, and open repositioning through the anterior approach Smith Peterson. Do installation of K-Wires and external fixation with hemispica. Given anti-tuberculosis drug for 12 months. In the monitoring for 2 years post-operatively, the patient reported an improvement.Conclusion: Hip Tuberculosis have a variety of mànifestasi similar to other diseases. Biopsy of the bone tissue lesions is a gold standard diagnosis for coxitis TB. However interpretation of the early picture of pelvic radiology can be a predictor outcome in the case of coxitis TB.